Teaching undergraduate nursing in mental health as allied to the consolidation of the Psychiatric Reform movement - Gizele da Conceição Soares Martins; Maria Angélica de Almeida Peres; Tânia Cristina Franco Santos; Paulo Joaquim Pina Queirós; Carolina Fraga Paiva; Antonio José de Almeida Filho (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To analyze the updating of mental health education in a Nursing Undergraduate Course concomitantly with the implementation of the Psychiatric Reform in the municipality of Volta Redonda. Method: Historical-social study with primary sources consisting of written and oral documents. The analysis, based on the main concepts of the Psychiatric Reform, was performed by the triangulation of data. Results: In a transitional phase of mental health models, the municipality studied developed strategies to develop psychiatric reform, of which the creation of CAPS stands out. At the same time, an agreement with the Undergraduate Nursing Course enrolled students, still in the 1990s, in all the mental health services of the municipality. The teachers of this course acted as nurses, one in care and another in mental health management, facilitating the teaching-assistance dialogue. Conclusion: The graduate students, to integrate as interns services, contributed to the change of the concepts that supported the mental healthcare, while the psychiatric reform developed. This was a successful strategy to stimulate the formation of a new logic and care to brings killed labor to services, since the course graduates opted for acting in CAPS.